Antifungal Imidazole‐Decorated Cationic Amphiphiles with Markedly Low Hemolytic Activity. Issue 32 (30th June 2016) - Benhamou, Raphael I.; Steinbuch, Kfir B.; Fridman, Micha
Abstract: Herein we report that an imidazole‐decorated cationic amphiphile derived from the pseudo‐disaccharide nebramine has potent antifungal activity against strains of Candida glabrata pathogens. In combination with the natural bis‐benzylisoquinoline alkaloid tetrandrine the reported antifungal cationic amphiphile demonstrated synergistic antifungal activity against Candida albicans pathogens. This unique membrane disruptor caused no detectible mammalian red blood cell hemolysis at concentrations up to more than two orders of magnitude greater than its minimal inhibitory concentrations against the tested C. glabrata strains. We provide evidence that potency against C. glabrata may be associated with differences between the drug efflux pumps of C. albicans and C. glabrata . Imidazole decorated‐cationic amphiphiles show promise for the development of less toxic membrane‐disrupting antifungal drugs and drug combinations. Abstract : Antifungal agents : Antifungal aminoglycoside‐derived cationic amphiphiles cause markedly low hemolysis (see graphic) as shown by an imidazole‐decorated cationic amphiphile derived from the pseudo‐disaccharide nebramine, which has potent antifungal activity against strains of Candida glabrata pathogens.